Improved exponential stability for time-varying systems with nonlinear delayed perturbations - Niamsup P. (2014)
In this paper, a new sufficient delay dependent exponential stability condition for a class of linear time-varying systems with nonlinear delayed perturbations is derived by using an improved Lyapunov-Krasovskii functional. The proposed exponential stability conditions are formulated in terms of the solution of Lyapunov differential equations. The approach allows for computation of the bounds that characterize the exponential stability rate of convergence of the solution. Compared with existing results, our conditions are shown to be less conservative. Numerical examples are given to illustrate the effectiveness of the obtained conditions. © 2008 Elsevier Inc. All rights reserved.